Teokrasi dan Musyawarah dalam Pemerintahan Nabi Muhammad Saw Mengenai Kajian Konstitusional atas Piagam Madinah - Habib Habiby Tambunan, Alreza Revaldo; Putra, Farandi Wiryanata; Latua, Abidin (Syekh Ali Hasan Ahmad Addary State Islamic University, 2025)
The Islamic system of government has undergone significant development throughout the history of the Muslim community. Beginning with the leadership of Prophet Muhammad SAW, governance was based on divine revelation and the principles of justice and consultation. The period of the Khulafaur Rasyidin continued this legacy by emphasizing shura (consultation) and leadership equality. However, a notable shift occurred during the Umayyad Dynasty, which introduced hereditary monarchy, followed by the Abbasid Dynasty, which developed a more complex governmental bureaucracy. This study addresses the characteristics of Islamic governance in each period and how these transformations affected the core principles of Islamic rule. The research employs a descriptive-qualitative method with a historical-comparative approach, aiming to analyze the dynamics and transformation of government systems from the Prophet Muhammad's era to the Abbasid Dynasty. The findings reveal that although core Islamic values such as justice, consultation, and adherence to Sharia remained foundational, the exercise of power shifted from collective to monarchical structures. This study concludes that socio-political contexts greatly influenced the form and implementation of governance in Islamic history.